Tax-benefit microsimulation: Feasibility study in Ethiopia - Andualem T. Mengistu; Kiflu G. Molla; Firew B. Woldeyes (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
The purpose of this study is to assess the feasibility of building a microsiumlation model of the Ethiopian tax and benefits system. We first provide a detailed describtion of the tax and benefits system of the country. This includes qualifying criteria, tax brakcets, and exemptions. We then describe household survey datasets available in the country and examine the nature of these datasets in terms of representativeness, completeness, and panel data structure. Finally, we provide assessments for whether each tax and benefits system can be microsimulatd given the rules and the nature of the data available.
Keywords: E62; H24; 330; tax; benefits; microsimulations; revenue